Critical national response in coping with Omicron variant in China, Israel, South Africa, and the United States - Jiao, Jun; Shi, Leiyu; Chen, Haiqian; Wang, Xiaohan; Yang, Manfei; Yang, Junyan; Liu, Meiheng; Sun, Gang (Frontiers in Public Health, 2023)
Objective: To analyze the effectiveness of prevention and control strategies and put forward further measures according to Omicron epidemiological characteristics, this study summarized national response during Omicron epidemic in four countries: China, Israel, South Africa, and the U.S. Methods: This study summarized prevention and control measures in China, Israel, South Africa, and the U.S. response to Omicron epidemic, and evaluated the effectiveness of measures. Results: After Omicron variant emerged, China and Israel adopted containment strategies, using the "dynamic zero" policy and country closure measures. Meanwhile, South Africa and the U.S. adopted mitigation strategies, which virtually abandoned social interventions and only focused on medical measures and vaccines. From the first reported Omicron cases day to Feb 28, 2022, the four countries reported the following Omicron cases: China reported 9,670 new confirmed cases and no deaths, with total deaths per million of 3.21; Israel reported 2,293,415 new confirmed cases and 2,016 deaths, with total deaths per million of 1,097.21; South Africa reported 731,384 new confirmed cases and 9,509 deaths, with total deaths per million reaching 1,655.708; the U.S. reported 3,042,743 new confirmed cases and 1,688,851 deaths, with total deaths per million reaching 2,855.052, much higher than other countries. Conclusion: Based on this study it seems that China and Israel adopted containment, and South Africa and the U.S. adopted mitigation strategies. A rapid response is a powerful weapon against Omicron epidemic.Vaccines alone will not get any country out of this crisis, Non-pharmacological measures should be used together10. According to the SPO model, this is desirable for future work: strengthening emergency management capacity, adhering to public health measures, promoting vaccination, and strengthening patient care and close contact management are the effective measures in coping with Omicron.